PENGARUH PERAWATAN PAYUDARA TERHADAP KELANCARAN ASI PADA IBU NIFAS - Halimah, Siti; Aldinda, Tharra Widadari; Anita, Wan; Wahyuni, Diana Rifka Yulia; Hikmah, Nurul (Ensiklopedia of Journal, 2025)
Abstract: Breast care is a way of showing directly to postpartum mothers how to care for breasts by providing stimulation to the breast muscles to facilitate breastfeeding. The purpose of this study is to determine the smoothness of breastfeeding of postpartum mothers after being given breast care. This study is a quasi-experimental research with a pre test and post test approach, the sample in this study is the first day postpartum women in the working area of the Sidomulyo Inpatient Health Center which amounted to 16 experimental groups and 16 control groups. Breast care in this study was carried out on the first to third day postpartum which was carried out 2 times a day with a duration of approximately 30 minutes. In the Pretest Intervention group, the average (11.13) and after breast treatment increased to (12.25) and a p value of 0.000 was obtained. Meanwhile, in the Pretest (11.00) and Post test (11.44) control groups, a p value of 0.008 was obtained. The results of the study using the Wilcoxon test obtained a p value < 0.05. The results of this study show that there is an effect of breast care on the smooth flow of breastfeeding in postpartum mothers in the working area of the Sidomulyo Inpatient Health Center. The advice that can be given, especially for the Sidomulyo Inpatient Health Center, is to recommend breast care that is provided continuously as an effort to increase exclusive breastfeeding.Keywords: Breast Care, Smooth Breastfeeding